Coastal upwelling trends under future warming scenarios from the CORDEX project along the Galician coast (NW Iberian Peninsula). (17th November 2016) - Alvarez, I.; Lorenzo, M. N.; deCastro, M.; Gomez‐Gesteira, M.
ABSTRACT: Upwelling Index trends derived from wind speed were analysed along the Galician coast using simulations from EURO‐CORDEX project (12.5 km). Data from this project were compared to ENSEMBLES and Cross‐Calibrated Multi‐Platform (CCMP) (25 km) data to investigate the performance of these high spatial resolution data in the ability to represent the evolution of Upwelling Index. Results suggest that differences between Upwelling Index derived from CCMP and modelled data exist all along the coast over the last decades. Both EURO‐CORDEX and ENSEMBLES data tend to overestimate Upwelling Index intensity (in absolute terms) regarding CCMP data. Future climate projections from EURO‐CORDEX show a significant strengthening trend in Upwelling Index intensity derived from wind data and in the frequency of strong upwelling events during the upwelling season (April–September).